Study of Mothers’ and Infants’ Life Events Affecting Oral Health (SMILE) birth cohort study: Cohort profile - Do, Loc; Ha, Diep; Bell, Lucy; Devenish, Gemma; Golley, Rebecca; Leary, Sam; Manton, David; Thomson, Murray; Scott, Jane; Spencer, J. Andrew (BMJ Journals, 2020)
Purpose: The long-term goal of the Study of Mothers’ and Infants’ Life Events Affecting Oral Health (SMILE) birth cohort study is to identify and evaluate the relative importance and timing of critical factors that shape the oral health of young children. It will then evaluate those factors in their inter-relationship with socioeconomic influences.